2023
DOI: 10.3389/fimmu.2023.1221097
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy and brain metastasis in lung cancer: connecting bench side science to the clinic

Alejandro Rios-Hoyo,
Edurne Arriola

Abstract: Brain metastases (BMs) are the most common form of intracranial malignant neoplasms in adults, with a profound impact on quality of life and traditionally associated with a dismal prognosis. Lung cancer accounts for approximately 40%–50% of BM across different tumors. The process leading to BMs is complex and includes local invasion, intravasation, tumor cells circulation into the bloodstream, disruption of the blood–brain barrier, extravasation of tumor cells into the brain parenchyma, and interaction with ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 162 publications
0
2
0
Order By: Relevance
“…Different clinical trials and retrospective studies have evaluated the effect of ICI alone or in combination with other interventions in lung cancer patients with BM suggesting the efficacy of ICI in patients with BM was worse than those without BM. 51 In addition, data from recent studies of ICIs in patients with NSCLC having brain metastases supported the notion that the brain was an immune privileged site. 52 , 53 , 54 Similarly, the current study also showed no survival benefit from ICIs + CT versus CT in patients with BM, even with anlotinib in combination, which may be due to the small sample size of enrolled patients with BM.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Different clinical trials and retrospective studies have evaluated the effect of ICI alone or in combination with other interventions in lung cancer patients with BM suggesting the efficacy of ICI in patients with BM was worse than those without BM. 51 In addition, data from recent studies of ICIs in patients with NSCLC having brain metastases supported the notion that the brain was an immune privileged site. 52 , 53 , 54 Similarly, the current study also showed no survival benefit from ICIs + CT versus CT in patients with BM, even with anlotinib in combination, which may be due to the small sample size of enrolled patients with BM.…”
Section: Discussionmentioning
confidence: 87%
“…The prognosis of ES‐SCLC with BM is dismal and only patients with asymptomatic BM or treated BM stable off steroids could be included in randomized controlled trials. Different clinical trials and retrospective studies have evaluated the effect of ICI alone or in combination with other interventions in lung cancer patients with BM suggesting the efficacy of ICI in patients with BM was worse than those without BM 51 . In addition, data from recent studies of ICIs in patients with NSCLC having brain metastases supported the notion that the brain was an immune privileged site 52–54 .…”
Section: Discussionmentioning
confidence: 99%